Using temporary dye marks to estimate ungulate population abundance in southwest Yukon, Canada - Hegel, Troy M.; Russell, Kyle; Jung, Thomas S. (Rangifer, 2012)
We describe the protocols of two mark-resight abundance surveys, using temporary dye-marks, for the Aishihik woodland caribou (Rangifer tarandus caribou) and wood bison (Bison bison athabascae) populations (herds) in the southwest Yukon Territory, Canada. We also provide recommendations based on experiences from these surveys for biologists and managers considering this approach. The Aishihik woodland caribou herd was the focus of intensive management in the 1990s aimed at recovering the herd. Following recovery activities, a target size of 2000 animals was determined and the Champagne-Aishihik Traditional Territory Community-Based Wildlife Management Plan recommended an estimate of the herd’s size be completed before the year 2013. We used an aerial mark-resight approach to estimate the herd’s size in March 2009. Caribou (n = 59) were marked from a helicopter with temporary dye, delivered via a CO2-powered rifle. Two independent resighting sessions were subsequently carried out via helicopter. The herd was estimated at 2044 animals (90% CI: 1768 – 2420) with an overall resighting rate of 0.47. The mean annual growth rate (λ) of the herd from 1997 – 2009 was 1.05 (SE = 0.01). The Aishihik wood bison herd was estimated at 1151 (90% CI: 998 – 1355). Our study suggests that ungulates temporarily marked with dye can be successfully used to obtain statistically sound population estimates.